Who am I as a leader? An analysis of leader identity among clinical consultants in Denmark - Cecchini, Mathilde (Politica, 2021)
Studies have emphasized the importance of leader identity for the development of public leaders since a strong leader identity is strongly correlated with active leadership behavior. In the literature, leader identity is often defined as “the extent to which an individual identifies as a leader”. In this article, I argue that leader identity is not only a question of strength but also of the substantial meaning individuals ascribe to this identity. Based on the literature on leader identity and a qualitative analysis of 21 semi-structured interviews with clinical consultants in Danish hospitals, the article identifies three different types of leader identity: the dominant leader, the engaging leader and the entrepreneur.